Effect of Different Modification Methods on Gelatinization Properties and Amylose Content of Kithul (Caryota urens) Flour - Wijesinghe, J.A.A.C.; Wicramasinghe, I.; Saranandha, K.H. (Pakistan Journal of Nutrition, 2016)
Detailed studies have been carried out on Kithul (Caryota urens) native and modified flour as two pre-gelatinized treatments (PGI and PGII), acid modified (AC) and dextrinized modification (DX) flour treatments to compare gelatinization properties and amylose content. Among all treatments, PG-II (modified with excess water at 75°C heat treatment) showed significant changes with higher gelatinization temperatures (TO = 74.02°C and TP = 80.51°C) and lower Conclusion temperature (TC = 90.04°C), gelatinization enthalpy (5.78 J/g) and amylose content (25.36). This study provides evidence that PGII is the most suitable modification treatment for native Kithul flour for introducing new flour source with an applicable form to meet specific needs with a view to effort expand application within the food industry.